Seasonal variability of coccolith fluxes in sediment traps of the Perdido and Coatzacoalcos regions in the Southern Gulf of Mexico - Felipe de Jesús García-Romero; Juan Carlos Herguera García; Jörg Bollmann; José Rubén Lara Lara; Mara Yadira Cortés Martínez; Amaru Márquez-Artavia (PLoS ONE, 2025)
We present new results of the coccolith fluxes in the Perdido and Coatzacoalcos areas of the Gulf of Mexico (GoM) and explore the environmental variables that may control them. The deep-water region of the GoM is known for its oligotrophic, nutrient-limited surface waters, which are relatively isolated from eutrophic waters near the coast; however, it is seasonally affected by nutrient-rich plumes of coastal waters that increase export production. Two sediment trap moorings located at a water depth of 1100 m collected settling particles from June 2016 to July 2017. The Perdido trap collected 47 species of coccoliths, and the Coatzacoalcos trap 56 species throughout the study period. Total coccolith fluxes showed a seasonal response in both trap locations, with lower fluxes during spring and summer, associated with highly stratified water column conditions that were evident in the Coatzacoalcos trap, and higher fluxes during late autumn and winter, associated with deepening mixed layer in response to cooling and to the strong “Nortes” winds. The Perdido trap showed higher total coccolith fluxes with an annual average of 3.1 x 10 9 ± 0.9 x 10 9 coccoliths per m -2 d -1 , than the Coatzacoalcos trap of 1.9 x 10 9 ± 1.1 x 10 9 coccoliths m -2 d -1 . The upper photic zone (mainly, Emiliania huxleyi and Gephyrocapsa oceanica ) showed high fluxes throughout the study period in both traps, reflecting the coastal shelf influence. Overall, three species dominated the composition of the coccolith fluxes in both areas: E. huxleyi , G. oceanica , and Florisphaera profunda , reaching 88% in the Perdido and 84% in the Coatzacoalcos trap. These results suggest that the coccolith export production in the Perdido and Coatzacoalcos traps is strongly influenced by the cooling and deepening of the mixed layer depth during autumn and winter, as well as advection processes between the continental shelf and the offshore region, and multifactorial processes such as loop current mesoscale eddies that affect the GoM.